Investigation into Chronic Low-Dose Ionizing Radiation Effect on Gene Expression Profile of Human HUVECs Cells: Chronic Low-Dose Ionizing Radiation Effect on Gene Expression Profile of Human Cell - Ansari, Mojtaba; Rezaei-Tavirani, Mostafa; Hamzeloo-Moghadam, Maryam; Razzaghi, Mohhamadreza; Arjmand, Babak; Zamanian Azodi, Mona; Khodadoost, Mahmood; Okhovatian, Farshad (Journal of Lasers in Medical Sciences, 2022)
Introduction: Understanding the molecular mechanism of chronic low-dose ionizing radiation (LDIR) effects on the human body is the subject of many research studies. Several aspects of cell function such as cell proliferation, apoptosis, inflammation, and tumorigenesis are affected by LDIR. Detection of the main biological process that is targeted by LIDR via network analysis is the main aim of this study. Methods: GSE66720 consisting of gene expression profiles of human umbilical vein endothelial cells (HUVECs) (a suitable cell line to be investigated), including irradiated and control cells, was downloaded from Gene Expression Omnibus (GEO). The significant differentially expressed genes (DEGs) were determined and analyzed via protein-protein interaction (PPI) network analysis to find the central individuals. The main cell function which was related to the central nodes was introduced. Results: Among 64 queried DEGs, 48 genes were recognized by the STRING database. C-X-C motif chemokine ligand 8 (CXCL8), intercellular adhesion molecule 1 (ICAM1), Melanoma growth-stimulatory activity/growth-regulated protein α (CXCL1), vascular cell adhesion molecule 1 (VCAM-1), and nerve growth factor (NGF) were introduced as hub nodes. Conclusion: Findings indicate that inflammation is the main initial target of LDIR at the cellular level which is associated with alteration in the other essential functions of the irradiated cells.